2019
DOI: 10.1186/s12873-019-0252-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of injuries presenting to the accident centre of Korle-Bu Teaching Hospital, Ghana

Abstract: Background Injuries directly lead to 5 million deaths every year, accounting for 9% of all deaths worldwide. While knowledge of the pattern of injuries is essential to plan health interventions to reduce the incidence of injuries, these are not thoroughly described in Ghana. The aim of this study was to describe the epidemiology of injuries seen at the Accident centre of the Korle-Bu Teaching Hospital, Ghana’s main referral hospital. Method A retrospective review of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 12 publications
3
20
0
2
Order By: Relevance
“…The most prevalent cause of injuries in our sample population was traffic injuries, but we observed that falls and interpersonal violence represented a proportionate amount of injury causes. This observation mirrors the general pattern of injured patients who present to the study site [ 26 ], and seems to be common in both developed and emerging countries [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…The most prevalent cause of injuries in our sample population was traffic injuries, but we observed that falls and interpersonal violence represented a proportionate amount of injury causes. This observation mirrors the general pattern of injured patients who present to the study site [ 26 ], and seems to be common in both developed and emerging countries [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…[ 1 ] The prevalence of occupational injuries among the injuries reported to tertiary teaching hospital in Ghana was 3%. [ 5 ] This discrepancy is due to the fact that the study was conducted in a multispecialty tertiary care centre with wide range of emergency cases covering all specialities and also minor injuries from the workplace which would have either gone unreported or been treated in other hospitals. Also, other studies have shown that, among those with work-related injuries about 60% of them has seen primary care physician.…”
Section: Discussionmentioning
confidence: 99%
“…In sub Saharan Africa, trauma results from gender-based violence, conflicts, motor vehicle crashes, and political unrest among others. The burden of injuries is said to be decreasing in developed countries and increasing in sub-Saharan Africa (Blankson, 2019). In South Africa, a middle-income country, major causes of trauma include road traffic injuries and violence.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, road traffic accidents are the main source of trauma. 25.5% of the road accidents involved motor cycles (Blankson ,2019). In Kenya, road traffic accidents are the leading cause injury (36%).…”
Section: Introductionmentioning
confidence: 99%